Evaluation of Lower Urinary Tract Symptoms (LUTS): Severity Score and Symptom Association - Pradhan, Tarun; Thapa, Baburam Dixit; Basnet, Pritha; Rimal, Surya Prasad; Basnet, Tulasha; Regmi, Mohan Chandra (Birat Journal of Health Sciences, 2019)
Introduction: Lower urinary tract symptoms (LUTS) is a group of symptoms relating to stages of micturation such as storage symptoms, voiding dysfunction and post micturation dysfunction. Overactive bladder symptom score (OABSS) is a questionnaires with scores which helps in evaluating the severity of symptoms.Objectives To find the incidence of women visiting with LUTS and to evaluate storage symptoms in LUTS (urgency, urge incontinence, frequency) using OABSS (overactive bladder symptom score) questionnaires.Methodology This is a prospective study done from February 2016 to February 2017. Patients visiting Department of Obstetrics and Gynaecology with lower urinary tract symptoms (LUTS) were enrolled in the study after informed consent. Patients were assessed for types of LUTS and data were filled in the performa. If patients had urgency, urge incontinence, increased day time frequency, then the patients were explained and asked overactive bladder symptom score questionnaire (OABSS) and noted. Patients were then examined for pelvic floor dysfunction and neurological abnormalities for identifying association with the symptoms. Statistical analysis was done using SPSS 11.5.Results Fifty-seven patients were enrolled with lower urinary tract symptoms (LUTS) during study period. Forty-six patients had overactive bladder symptoms (OABS). LUTS were found in age ranging from 21 to 80 years. Majority of patients visiting out-patient department with LUTS were found to have urgency, urge incontinence, increased day time frequency, nocturia. Patients with urgency and urge incontinence showed significant correlation with increasing likert score of OABSS (p